華人地區數學素養教育效率比較 Educational Efficiency of Mathematical Literacy: A Comparison of Four Ethnically Chinese Regions - 鄭永福 Yung-Fu Cheng; 許瑛玿 Ying-Shao Hsu; 李哲迪 Che-Di Lee (National Taiwan Normal University, 2018)
本研究利用國際學生能力評量計畫 2012 年資料比較臺灣（只包括人口數大於 100 萬的七個大城市）、上海、香港與新加坡等四個華人地區的數學素養教育效率，並從教育效率的角度探討這四個地區數學教育的公平性。資料包絡分析法及效率分解法之分析結果顯示，臺灣與上海的「綜合效率」（含地區、學校與個人教育效率）、「地區與學校效率」與「地區系統效率」都是最高。然而，歸因於個人之無效率以臺灣與上海最高，歸因於學校之無效率在四個地區無顯著差異，歸因於地區之無效率以香港最高。在四個地區教育公平性方面，在高與低綜合教育效率學生之間，個人、學校與地區三個層級的無效率存在差異。具體而言，在個人層級，臺灣的無效率差異最大、上海次之；在學校層級，新加坡的無效率差異最大、臺灣次之；在地區層級，僅上海存在差異。總結而言，臺灣雖是數學素養教育效率最佳的兩個地區之一，然而，歸因於個人之無效率仍有相對較高的數值，且個人與學校之無效率也存在高與低教育效率學生之間差異過大的問題。此結果顯示，臺灣在個人和學校層級的教育效率仍有改進的空間。 This study uses data from the Programme for International Student Assessment 2012 to compare the educational efficiency of mathematical literacy and explore the educational equality of mathematics with educational efficiency across four ethnically Chinese regions, including Taiwan (containing seven cities with a population greater than 1 million), Shanghai, Hong Kong, and Singapore. Data envelopment analysis and decomposition of efficiency revealed that Taiwan and Shanghai have the highest overall efficiency (the total of the regional, school, and individual levels), regional plus school efficiency (the total of the regional and school levels), and regional system efficiency. However, Taiwan and Shanghai have the most inefficiency at the individual level, and Hong Kong has the most inefficiency at the regional level. At the school level, there was no significant difference in terms of inefficiency among the four regions. Regarding educational equality among the four regions, there were significant differences in educational inefficiency at the individual, school, and regional levels between students with high and low overall educational efficiency. Specifically, at the individual level, Taiwan had the largest inefficiency difference between students with high and low overall efficiency, followed by Shanghai. At the school level, Singapore had the largest inefficiency difference, followed by Taiwan. At the regional level, only Shanghai had a significant difference in inefficiency. In summary, although Taiwan is one of the top two of these four regions in terms of the educational efficiency of mathematical literacy, it has the most educational inefficiency at the individual level and higher inefficiency differences at the individual and school levels between students with high and low overall efficiency. This indicates that Taiwan can still improve its educational efficiency.